Stimulation of the Development of Moral and Social Aspects in Efforts to Improve the Mental Health of School-Age Children - Yuniar Sari, Niken; Elita, Veny; Sari, Tesha Hestyana; Fitri, Aminatul; Rustam, Murfardi (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
The stages of psychosocial development of school-age children are in the industrial phase, namely the ability to produce work, interact and achieve in learning. If school children are unable to achieve their development optimally, then school children will experience low self-esteem. Stimulation of moral and social development of school-age children is an important aspect in supporting psychosocial growth because it can affect social abilities in the future. Without proper stimulation, children can experience obstacles in development that can cause problems such as low self-esteem and lack of self-confidence. The purpose of this service is to stimulate the development of moral and social aspects of school-age children. The method used in this service activity is to carry out stimulation on 30 school-age children by providing stimulation on the moral and social development aspects of school-age children. The results of this service activity show that there is an increase in the moral aspect by 2.7% and the social aspect by 11.9% in school age children. Therefore, stimulation of the development of this aspect is recommended as a health promotion to improve the development of moral and social aspects of school-age children in the mental health service setting in the community.